HUJJAH QAUL SHAHABAT DALAM PERSPEKTIF HUKUM ISLAM: HUJJAH QAUL SAHABAT - Nurkholis; Muhammad Singgih (An Naba, 2018)
Rasulullah SAW, said, "That the best generation is the generation in my day then the generation afterwards then the generation afterwards ...". The generation in which the Prophet was sent is the generation of friends. They are the best generation, from the aspect of the faith they are very strict about Islamic teachings, and love Allah and His Messenger more than anything. This can be seen from the story of the friends in maintaining their aqeedah, although it must be tortured and beaten by various tortures and insults from the infidels of Quraysh. They are the generation that we should set as an example, both from the strength of the faith, from its application in daily life and the efforts of the Companions to not just become pious themselves but it is they who spread the teachings of Islam (aqeedah, morals and sharia) to others. The scholars categorize qaul as-shahabi as one source of legal decision that is still contested for its validity. In contrast to the Qur'an, the sunnah, ijma ’and the qiyas of the ulama have agreed to it as a source of law-making in Islam. What is meant by jumhur ulama here are the four Imams of the school who don't teach. Therefore, to find out the opinions of the scholars who differed on the validity of qaul as-shahabi, the author tries to give a little picture of this in this simple paper.